2022
DOI: 10.1155/2022/7346408
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors, Musculoskeletal Health, Physical Fitness, and Occupational Performance in Firefighters: A Narrative Review

Abstract: Introduction. Firefighting is a strenuous occupation that requires firefighters to be in peak physical condition. However, many firefighters have risk factors for cardiovascular disease, impaired musculoskeletal health, and are not physically fit for duty, which all negatively impact their occupational performance. Therefore, the aim of this review is to determine the relationship between cardiovascular disease risk factors, musculoskeletal health, physical fitness, and occupational performance in firefighters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 103 publications
0
17
1
2
Order By: Relevance
“…Moreover, studies have shown that HRV was linked to overtraining and overuse, providing a potential link between HRV and MSH, 54,55 particularly in the firefighter population, which is known to be a physically demanding profession. In this current study, higher levels of vigorous weekly physical activity had a protective effect on the prevalence of MSIs of firefighters, which is not unexpected, given the protective effect of physical activity on musculoskeletal health, which is well documented in firefighters 5,29 . This is in contrast to a previous study in this population, which noted higher weekly physical activity was related to an increase in MSIs 56 .…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Moreover, studies have shown that HRV was linked to overtraining and overuse, providing a potential link between HRV and MSH, 54,55 particularly in the firefighter population, which is known to be a physically demanding profession. In this current study, higher levels of vigorous weekly physical activity had a protective effect on the prevalence of MSIs of firefighters, which is not unexpected, given the protective effect of physical activity on musculoskeletal health, which is well documented in firefighters 5,29 . This is in contrast to a previous study in this population, which noted higher weekly physical activity was related to an increase in MSIs 56 .…”
Section: Discussioncontrasting
confidence: 91%
“…During physically intense duty–related activity, firefighters often reach or even exceed their maximum age-predicted heart rates, 2,4 with many activities requiring forceful repetitive muscular contractions. This necessitates that firefighters maintain good cardiovascular and musculoskeletal health to assist in performing their duties with sufficient speed and efficiency 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…В большинстве групп недельная ФА до ИМ была низкой. На примере исследований с пожарными и с медицинскими работниками наибольшее число осложнений со стороны сердечно-сосудистой системы также отмечалось в случаях минимального уровня ФА [26,27].…”
Section: Discussionunclassified
“…Por la dificultad de la actividad profesional de un bombero es necesario hacer una correcta selección inicial, ajustada a los requerimientos del desempeño de puesto (Xu et al, 2020), pero sin olvidar la importancia de realizar un seguimiento y evaluación de competencias y desempeño longitudinal, pues su estado general puede verse afectado si su formación o entrenamiento no son acertados ni regulares (Llinás, 2004). Existe una abrumadora evidencia científica sobre la relación significativa entre la aptitud física, los factores de riesgo, y el desempeño profesional, aunque es necesaria una mayor evidencia entre la aptitud muscular y el rendimiento laboral (Ras et al, 2022).…”
Section: Fuente: Propiaunclassified